2019
DOI: 10.3390/geosciences9060248
|View full text |Cite
|
Sign up to set email alerts
|

UAV and Airborne LiDAR Data for Interpreting Kinematic Evolution of Landslide Movements: The Case Study of the Montescaglioso Landslide (Southern Italy)

Abstract: Airborne remote sensing systems are increasingly used in engineering geology and geomorphology for studying and monitoring natural hazardous scenarios and events. In this study, we used two remote sensing monitoring techniques, i.e., light detection and ranging (LiDAR) and unmanned aerial vehicles (UAV) to analyze the kinematic evolution of the Montescaglioso landslide (Basilicata, Southern Italy), a large rain-triggered landslide that occurred in December 2013. By comparing pre- and post-event LiDAR and UAV D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…Some authors do not mention any specifics of the UAV survey. UAV was used by [19][20][21] to survey landslides and rockfalls.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors do not mention any specifics of the UAV survey. UAV was used by [19][20][21] to survey landslides and rockfalls.…”
Section: Introductionmentioning
confidence: 99%
“…The use of sUAVs in disaster reconnaissance prevents researchers and surveyors from having to enter many high-risk areas and reduces the time spent collecting surveyed data at every desired point. A recent example of high resolution sUAV data acquisition is Pavelka et al [16] of the Pista Geoglyph in Peru, and expertise with sUAVs (and LiDAR) as shown in Pellicani et al [17] demonstrates that sUAVs support and compliment geomorphic interpretations of disaster sites. Creating useful and accurate models with SfM software requires a series of photos at various normal and oblique angles that eventually tie into ground control points (GCPs) in a 3D reconstructed model.…”
Section: Methods Of Preliminary Suav Reconnaissance and Modeling In 2016mentioning
confidence: 99%
“…Remote-sensing techniques, based on terrestrial or air-or space-borne sensors, are commonly used to detect and monitor morphological changes as slope processes and valley floor modifications [10][11][12][13][14][15][16][17]. Recent advances of these technologies and better availability of high-resolution digital terrain models (DTMs) [18][19][20] provide the opportunity to perform detailed studies aimed at the assessment and analysis of morphological changes (e.g., landslides and soil erosion induced by rainfall) in small mountain basins [12,21].…”
Section: Introductionmentioning
confidence: 99%
“…The issue of ground surface differences in the context of morphological changes, using high-resolution DTMs, were widely described for more than 10 years [21][22][23][24][25][26]. The increasing availability of high-resolution DTMs, such as those derived from light detection and ranging (LiDAR) technology and unmanned aerial vehicles (UAV), extends the applicability and potentialities of geomorphological and topography-based approaches for both landslide recognition, mapping [20][21][22][23][27][28][29][30][31] and the characterization of slopes dynamics [32][33][34][35], as well as surface modeling and monitoring [3,12,15,19,29,33].…”
Section: Introductionmentioning
confidence: 99%